MENINGKATKAN KETERAMPILAN BERBICARA DALAM MATERI PEMBELAJARAN REMEDIAL MELALUI METODE COMMUNITY LANGUAGE LEARNING (CLL) - Mochlis Ekowijayanto (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2019)
This research is concerned about learning English which sometimes seems to frighten students in a class where they cannot express something with a sense of confidence. The reason students score poorly on English subjects is due to several aspects that students must understand: pronunciation, grammatical structure, vocabulary, and intonation. Community Language Learning (CLL) shows how effective and efficient English language must be taught. Thus, this study was reported qualitatively to observe how Community Language Learning (CLL) was able to improve students' speaking skills in remedial learning Materials for eighth grade students at SMP Nurul Jadid with a total of 26 students. Observation sheets and score assessment sheets are made to collect data in considering the names of students who have low grade criteria. Fluency, pronunciation, expression, vocabulary, and content are used as instruments to analyze their performance. The method of this research approach is Classroom Action Research which reveals that students feel comfortable to join the learning experience, and its effect on their competence in speaking skills with an increasing amount during going through stage 2 cycles; post-test 1 and post-test 2. Community Language Learning (CLL) is considered an effective and efficient method because it contributes to the prominent effects of speaking skills.